Analisis Sentimen Terhadap Popularitas Partai Pendukung Capres 2024 di Twitter Menggunakan Algoritma Naive Bayes Classifier - Faroek, Dewi; Yusuf, Muhammad; Syatauw, Grace (Universitas Islam Balitar, 2023)
In accordance with the democratic system of government, Indonesia allows each political party or combination of parties running in the general election to nominate its own presidential and vice presidential candidates, as long as these candidates meet legal requirements. Presidential elections are scheduled for 2024. A political figure who wants to run for president at that time will have to rely heavily on public opinion for support. As the 2024 election approaches, political parties are increasingly turning to social media to spread their messages and increase their support. The aim of this research is to compare the level of support for the two leading candidates for president and vice president in 2024 on Twitter to determine the proportion of tweets that are positive, negative, or neutral.The aim of this research is to compare the level of support for the two main candidates for president and vice president in 2024 on Twitter to determine the proportion of tweets that are positive, negative, or neutral.